Upward Shifts in the Internal Representation of Frequency Can Persist Over a 3-Year Period for Cochlear Implant Patients Fit With a Relatively Short Electrode Array - Dorman, Michael F.; Natale, Sarah C.; Noble, Jack H.; Zeitler, Daniel M. (Frontiers in Human Neuroscience, 2022)
Patients fit with cochlear implants commonly indicate at the time of device fitting and for some time after, that the speech signal sounds abnormal. A high pitch or timbre is one component of the abnormal percept. In this project, our aim was to determine whether a number of years of cochlear implant use reduced perceived upshifts in frequency spectrum and/or voice fundamental frequency. The participants were five individuals who were deaf in one ear and who had normal hearing in the other ear. The deafened ears had been implanted with a relatively short (16 mm) electrode array which resulted in signal input frequencies being directed to locations in the spiral ganglion that were between one and two octaves higher than the input frequencies. The patients judged the similarity of a clean signal (a male-voice sentence) presented to their implanted ear and candidate, implant-like, signals presented to their normal-hearing ear. Matches to implant sound quality were obtained, on average, at 8 months after device activation (Time 1) and at 35 months after activation (Time 2). At Time 1, the matches to CI sound quality were characterized, most generally, by upshifts in the frequency spectrum and in voice pitch. At Time 2, for four of the five patients, frequency spectrum values remained elevated. For all five patients F0 values remained elevated. Overall, the data offer little support for the proposition that, for patients fit with shorter electrode arrays, cortical plasticity nudges the cortical representation of the CI voice toward more normal, or less upshifted, frequency values between 8 and 35 months after device activation. Cortical plasticity may be limited when there are large differences between frequencies in the input signal and the locations in the spiral ganglion stimulated by those frequencies.